Slip Velocity and Temperature Jump on Dissipative CASSON Fluid with CATTANEO-CHRISTOV Heat Flux Model: Spectral Relaxation Method - Gangadhar, K.; V. Ramana, K.; Kannan, T.; Rushi Kumar, B. (International Journal of Engineering and Technology, 2018)
A numerical analysis is performed for investigating the slip flow of a viscous dissipative Casson fluid towards a stretching sheet with Cattaneo-Christov heat flux and variable viscosity. The nonlinear partial differential equations are transformed with appropriate similarity variables into a system of nonlinear ordinary differential equations. Numerical solutions are carried out by using efficient Spectral relaxation method. Notable accuracy of the present results has been obtained with previous results in a limiting sense from the literature. It is found that thermal relaxation time has an inverse relationship with the fluid temperature. Interestingly, the fluid velocity is gradually decreasing with higher values of slip factor.Â Â Â